UV/VUV and photolysis of sulfamethazine - Minzini Ilaria (Proceedings of the International Symposium on Analytical and Environmental Problems, 2019)
In this work, UV and UV/VUV photolysis of sulfamethazine was investigated. Sulfamethazine is one of the most often used antibioticum, wich can be detected in soils and surface water. The applied light sources were low-pressure mercury vapour lamps having identical geometry and electric parameters. One of the light sources amitts only 254 nm UV light, while the other one emitts both 254 nm UV and 185 nm VUV light. Both UV and UV/VUV photolysis were found to be effective in the transformation of sulfamethazine, but COD decrease was observed only in the presence of VUV light. In parallel with the transformation of sulfamethazine, H2O2 formation was detected. Its concentration reached higher value in the case of UV/VUV than in UV radiation. Spectrophotometric measurements suggested that dissolved oxygen has effect on the formed interemdiates in both UV and UV/VUV photolysis. Transformation rates were determined in purified wastewater and tap water and compared to the values determined in Milli-Q water. Results showed that these mild matrices decreased the transformation rates in both cases. The inhibition effect in more pronounced in the case of UV photolysis.